2005
DOI: 10.5194/hess-9-193-2005
|View full text |Cite
|
Sign up to set email alerts
|

Variability in stream discharge and temperature: a preliminary assessment of the implications for juvenile and spawning Atlantic salmon

Abstract: Abstract. This study focuses on understanding the temporal variability in hydrological and thermal conditions in a small mountain stream and its potential implication for two life stages of Atlantic salmon (Salmo salar) -stream resident juveniles and returning adult spawners. Stream discharge and temperature in the Girnock Burn, NE Scotland, were characterised over ten hydrological years

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 64 publications
1
52
0
Order By: Relevance
“…Welton et al, 1999). Based on the data period 1994, Tetzlaff et al (2005b concluded that discharges less than 0.3 m 3 s À1 inhibited access to the burn. The current analysis for a longer period showed minimum mean daily discharges for entry for each year ranging between 0.10 (1972) and 1.62 (1987) m 3 s À1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Welton et al, 1999). Based on the data period 1994, Tetzlaff et al (2005b concluded that discharges less than 0.3 m 3 s À1 inhibited access to the burn. The current analysis for a longer period showed minimum mean daily discharges for entry for each year ranging between 0.10 (1972) and 1.62 (1987) m 3 s À1 .…”
Section: Discussionmentioning
confidence: 99%
“…Instantaneous discharges vary between ca. 0.04 m 3 s À1 in the summer (Malcolm et al, 2003) and > 30 m 3 s À1 during floods (Tetzlaff et al, 2005b). Most high discharge events occur between late autumn and early spring, though they can occur throughout the year (Tetzlaff et al, 2007a).…”
Section: Study Catchmentmentioning
confidence: 99%
“…With climate change, an increased discharge during winter, spring and autumn was observed (Birsan et al 2005) and with the predicted advance of peak flows in spring (Jasper et al 2004;Horton et al 2006) the timing could overlap fry emergence. Fry, around the time of emergence, is considered to be the live stage most sensitive to high floods (Jensen and Johnsen 1999;Cattanéo et al 2002;Tetzlaff et al 2005) whereas egg scouring is thought to occur only with extreme events (Cattanéo et al 2002). However, only a slight increase in discharge could result in significant egg damage (Montgomery et al 1996) and high discharges during incubation time and emergence was found to be inversely related to year-class-strength of brown trout (DeVries 1997;Spina 2001;Cattanéo et al 2002).…”
Section: Effect Of Changes In Temperatures and High Discharge On Spawmentioning
confidence: 99%
“…Furthermore, atmospheric warming in combination with projected reductions in summer flow is expected to increase river temperatures [10]. If we translate these impacts to potential consequences for the proliferation of the salmon, and thus the success of achieving related policy objectives, we obtain the following factors [30][31][32][33][34][35]:…”
Section: Step 2: Climate Impacts On Rhine Salmon Habitatsmentioning
confidence: 99%